EIB Working Papers 2019/01 - Blockchain, FinTechs and their relevance for international financial institutions (Volume 2019/1) - Davradakis, Emmanouil (European Investment Bank, 2019)
This paper provides an introduction to financial technology and blockchain, while exploring:the impact of FinTechs and TechFins on the financial sector,a description of blockchain technology and its applications, with a focus on cryptocurrencies,the impact on financial inclusion,risks and challenges,applications for international financial institutions and their clients.